The Impact of Software Pedagogy on Architectural Creativity: Finding the Appropriate Method and Time for Teaching Software to Architecture Students - S. M.A. Ahmadi Tabatabaie; S. M. Moosavi (Fanāvarī-i āmūzish, 2023)
Background and Objectives: The rapid advancement of computer technology has revolutionized various aspects of work and life, emphasizing the need for training and proper utilization of digital tools. Architectural software has become integral to the design process, enabling architects to explore new methods. However, concerns have arisen regarding the impact of software on creativity and innovation. This study aims to determine the appropriate timing and method for teaching software to architecture students while mitigating the negative effects on creativity. The findings will contribute to the development of more effective software training approaches in architecture schools and design firms. While technology offers benefits such as increased design speed and visualization, a balance between digital tools and traditional methods should be maintained in architectural education.Materials and Methods: The study adopts a qualitative approach, involving activities such as observation, interviews, and extensive participation in research activities to obtain firsthand information about the research subject. Qualitative research encompasses various data collection methods such as field research, observation or participation, and in-depth interviews. In the initial phase, the documentary method and library study were employed to establish the theoretical foundations of the research topic. In-depth interviews were conducted to gather information from experts in the field of architectural education. Data analysis involved content analysis, where the components of the collected text were categorized and counted. The independent variables of the research are the correct method and timing of teaching architectural software to students, while the dependent variable is the improvement of students' efficiency and benefit from learning the software. The findings were derived from the analysis of the interview responses and logical reasoning.Findings: The findings of the research indicate that students entering the field of architecture should first develop a solid foundation in hand drawing and design principles before delving into architectural software. Early exposure to software without a proper understanding of architecture can hinder creativity and result in the production of complex forms devoid of purpose and spatial understanding. It is recommended that students establish a strong connection between their hand, eye, and mind through freehand drawing and creative thinking before transitioning to digital software. The concept stage of design is best approached through manual sketches and modeling, while software can be utilized in later stages. Simultaneous teaching of software alongside other architectural subjects may lead to information overload and reduced focus. A progressive and integrated approach to teaching software within the curriculum is suggested to enhance students' practical application of software tools. This research provides insights for developing an effective educational method that prepares students for the job market while fostering their creativity and architectural understanding.Conclusions: The research findings suggest that students should learn architectural software after developing a foundation in hand drawing and design principles. Starting software training too early can hinder creativity and result in superficial designs. Teaching software alongside other architectural subjects in a progressive and integrated manner is recommended. Practical, project-based training helps students understand software features and promotes lasting learning. Unnecessary software components should be avoided to prevent confusion. Universities should modify their programs to meet students' needs in the job market and provide comprehensive software education.